2018
DOI: 10.1148/radiol.2017170550
|View full text |Cite
|
Sign up to set email alerts
|

Linearity, Bias, and Precision of Hepatic Proton Density Fat Fraction Measurements by Using MR Imaging: A Meta-Analysis

Abstract: Purpose To determine the linearity, bias, and precision of hepatic proton density fat fraction (PDFF) measurements by using magnetic resonance (MR) imaging across different field strengths, imager manufacturers, and reconstruction methods. Materials and Methods This meta-analysis was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic literature search identified studies that evaluated the linearity and/or bias of hepatic PDFF measurements by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
238
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 261 publications
(261 citation statements)
references
References 92 publications
18
238
0
5
Order By: Relevance
“…Only small, although statistically significant, differences were observed among the three MR imagers for both readers. Particularly, there was a trend for slightly higher PDFF values on the Philips scanners compared with those on the GE platform, which is consistent with the results from a recent large‐scaled meta‐analysis . The reason for these findings is uncertain at this point, but two factors could possibly account for this observation: first, incompletely corrected T 1 ‐bias is thought to be a significant source of error in chemical shift‐encoding‐based fat quantification and may induce PDFF overestimation, as outlined below.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Only small, although statistically significant, differences were observed among the three MR imagers for both readers. Particularly, there was a trend for slightly higher PDFF values on the Philips scanners compared with those on the GE platform, which is consistent with the results from a recent large‐scaled meta‐analysis . The reason for these findings is uncertain at this point, but two factors could possibly account for this observation: first, incompletely corrected T 1 ‐bias is thought to be a significant source of error in chemical shift‐encoding‐based fat quantification and may induce PDFF overestimation, as outlined below.…”
Section: Discussionsupporting
confidence: 84%
“…In patients, previous studies on steatosis quantification have shown high linear correlation and small mean bias in MRI‐determined PDFF ranging from 0.9–3.7% across two and three different MRI platforms. In our study, the reproducibility of MRI‐determined PDFF in lumbar bone marrow was comparable to or even better than that reported for liver fat quantification, possibly owing to the inherent heterogeneity of steatosis across the liver (ie, because of different ROI locations) . Only small, although statistically significant, differences were observed among the three MR imagers for both readers.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Over the last decade, emerging quantitative magnetic resonance imaging (MRI) biomarkers of hepatic steatosis such as proton density fat fraction (PDFF) have been developed, measured using confounder‐corrected chemical shift‐encoded MRI (CSE‐MRI). There has been a tremendous amount of work evaluating the bias, precision, reproducibility, and repeatability of CSE‐MRI to quantify PDFF in the liver . Despite this work there is a relative paucity of data investigating the variation of liver PDFF during the day, between days, as well as variation in liver PDFF resulting from hydration status and meals.…”
mentioning
confidence: 99%